The development of automatic fish feeder / Muhammad Adib Idham Mohd Salehin ... [et al.] - Mohd Salehin, Muhammad Adib Idham; Mahmod @ Wahab, Rohidatun; Hussin, Norasikin; Mohd Fohimi, Nor Azirah; Mohd Nasir, Siti Shareeda (Universiti Teknologi MARA, Kedah, 2023)
An automatic fish feeder is an electronic device that will automatically feed the fish at a predetermined time especially when the owners are not nearby. Nowadays, many people start keeping fish as their pet either as a hobby or as therapy. However, fish owners who are very busy or away for a long time will have trouble in giving enough food for their fish. Therefore, this device will help fish lovers to feed their fish every day. In this work, the automatic fish feeder uses Arduino’s microcontroller to set the programmed and servo motor to control the movement of the Archimedes screw attached, so that it will store and pour the fish food according to the programmed set. This automatic fish feeder container has been designed using Solid Work software and has been fabricated using 3D printing. The container comes with 5 parts which are the body, top cover, Arduino microcontroller’s cover, Archimedes screw and the servo motor stand. This automatic fish feeder will start functioning immediately after the power source is connected. As for the result, the automatic fish feeder drops a certain amount of fish food from its storage into the aquarium. The amount of fish food can be set according to the size of the tank. For this project, the amount of fish food drops from the automatic fish feeder is an appropriate amount for an aquarium of 2 feet in size and has been set to function three times a day which is every eight hours. However, if it is attached to a bigger tank, it can be set up longer so that more food will drop into the fish tank. Therefore, people can still ensure their fish foods are adequate even though they are too busy to manage it by themselves.